DENSITAS ENERGI PADA PANEL SURYA DENGAN VARIASI JUMLAH DAN SUDUT REFLEKTOR - Muhammad Rizali (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2018)
The use of solar energy is increasingly needed to be improved, so engineering is needed to optimize the energy obtained. One of the engineering done is to install a mirror as a reflector that directs sunlight right into the solar panel. The factors studied were the effect of the numbers (1,2,3 and 4 reflectors) and the reflector angle (60°, 65°, 70°) on the solar panel output power, and the ratio of the power to the projection area of the installation site (power density). The method performed is with the light of the spotlight in the room, without any other light source, then measured the current and the output voltage of the solar panel. The result is that the use of reflectors has an effect on the output power of solar panels, where the highest power and density are obtained on the use of 4 reflectors at an angle of 70° (1.04 W / m2), due to solar radiation collected all about the solar panel. The recommended use is 2 reflectors at an angle of 70°, with consideration of the practicality of the installation of the apparatus, and its high enough density (0.9935 W/m2). Keywords: solar panel, reflector, energy density, reflector count, reflector angle